ANALISIS KONTRIBUSI PUNGUTAN PAJAK BUMI DAN BANGUNAN TERHADAP PENDAPATAN ASLI DAERAH DI KABUPATEN BREBES - Amsirun, amsirun (Jurnal Strategik, 2019)
Abstract This study is entitled "Analysis of the Contribution of Land and Building Tax Collection to Local Revenue in Brebes Regency". The objectives to be achieved in this study are: a. To find out how much the contribution of land and building tax to local taxes in Brebes Regency. b. To find out how much the contribution of Land and Building Taxes on Regional Original Revenue in Brebes Regency. c. To find out how much the level of elasticity of Land and Building Taxes on the realization of Local Revenue in Brebes Regency. d. To find out the projected receipt of Land and Building Tax in the next five years in Brebes Regency. This type of research used in this study is a case study at the Department of Revenue and Financial Management (DPPK) in Brebes Regency. While the research method used is the Study of Literature, which is looking for data about things or variables in this case in the form of notes, literature books, newspapers, magazines, minutes of meetings and so on. And Communication Techniques, namely how to collect data through contacts or personal relationships between data collectors and data sources. The results showed that the contribution of land and building tax to regional taxes during the period 2009-2018 the contribution of land and building tax to local taxes in Brebes Regency was fluctuating, with an average of 69.29%, it could be said that the contribution was quite optimal because the nominal was already optimal. reach above 50%. While the contribution of land and building tax to regional original income during the 2009-2018 period the contribution of land and building tax to regional original income in Brebes Regency was 23.74%, this can be said to be less than optimal because the nominal has not reached 50%. Then the level of elasticity of the collection of Land and Building Taxes on the realization of Local Revenue during the period 2009-2018 the level of elasticity of the collection of Land and Building Taxes in Brebes Regency an average of 3.99% or rounded to 4% and is elastic because the nominal is more than 1 And the Projection of Land and Building Tax Revenue for the next five years in Brebes Regency the value of the linear trend equation is as follows: Y = 23,550,559,105 + 1,177,295,404 X means that if there is no change in PBB (Y) then the Regional Original Income is Rp. 23,550,559,105 and if there is an increase in PBB by 1 unit of rupiah the Regional Original Revenue will increase by Rp. 1,177,295,404 Keywords: Contribution, Land and Building Tax, Regional Original Revenue